Spatiotemporal Pattern of Neuroinflammation After Impact-Acceleration Closed Head Injury in the Rat - Servan Rooker; Sebastian Jander; Jos Van Reempts; Guido Stoll; Philippe G. Jorens; Marcel Borgers; Jan Verlooy (Mediators of Inflammation)
Inflammatory processes have been implicated in the pathogenesis of traumatic brain damage. We analyzed the spatiotemporal expression pattern of the proinflammatory key molecules: interleukin-1β, interleukin-6, tumor necrosis factor-α, and inducible nitric oxide synthase in a rat closed head injury (CHI) paradigm. 51 rats were used for RT-PCR analysis after CHI, and 18 for immunocytochemistry. We found an early upregulation of IL-1β, IL-6, and TNF-α mRNA between 1 h and 7 h after injury; the expression of iNOS mRNA only revealed a significant increase at 4 h. After 24 h, the expression decreased towards baseline levels, and remained low until 7 d after injury. Immunocytochemically, IL-1β induction was localized to ramified microglia in areas surrounding the primary impact place as well as deeper brain structures. Our study shows rapid induction of inflammatory gene expression that exceeds by far the primary impact site and might therefore contribute to tissue damage at remote sites.